If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(t + -1) = 2(2t + -4) Reorder the terms: 6(-1 + t) = 2(2t + -4) (-1 * 6 + t * 6) = 2(2t + -4) (-6 + 6t) = 2(2t + -4) Reorder the terms: -6 + 6t = 2(-4 + 2t) -6 + 6t = (-4 * 2 + 2t * 2) -6 + 6t = (-8 + 4t) Solving -6 + 6t = -8 + 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. -6 + 6t + -4t = -8 + 4t + -4t Combine like terms: 6t + -4t = 2t -6 + 2t = -8 + 4t + -4t Combine like terms: 4t + -4t = 0 -6 + 2t = -8 + 0 -6 + 2t = -8 Add '6' to each side of the equation. -6 + 6 + 2t = -8 + 6 Combine like terms: -6 + 6 = 0 0 + 2t = -8 + 6 2t = -8 + 6 Combine like terms: -8 + 6 = -2 2t = -2 Divide each side by '2'. t = -1 Simplifying t = -1
| x-27=8 | | 7p+12q=83 | | 6(8-a)=36 | | 4x+10y=76 | | -7(v+1)=3v-7+2(2v+8) | | 9x+3(33-4x)=78 | | 38=-2w+4(w+6) | | -16t(2+t)=0 | | 5-3(x-4)=15 | | 27z^2-46z=0 | | (X+3)(x-15)= | | 7v+3=-8(v+9) | | (X-3)(x+15)= | | j^2+22j=0 | | (X-3)(x-15)= | | (X-15)(x-3)= | | (x+40)(x)=6000 | | (X+15)(x-3)= | | -8x+6(x+3)=36 | | (X+15)(x+3)= | | 3d+5=5d-7 | | x^4-2x^2-45=0 | | 2x^2+7a+6=0 | | -2w+19=5(w+8) | | m^2+10m-11=0 | | -c+4(8-c)=43 | | 16t^2=32t | | j^2-35j=0 | | 3*w+2=W+4*2 | | 1/3x-2=3 | | h^2-18h=0 | | n^2-38n=0 |